2008
DOI: 10.3758/lb.36.4.290
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for the interchangeability of an avoidance behavior and a negative occasion setter

Abstract: 290Avoidance behavior is an instrumental response that prevents the occurrence of an aversive event. It is a common phenomenon in life, since a great deal of our activity is performed to avoid the occurrence of negative or aversive stimuli. In a typical study of avoidance learning, a warning signal (A) is presented and followed by an aversive unconditioned stimulus (US), unless the participant performs a designated response (R). For example, a tone (A) is presented and is followed by an electric shock (US), un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 18 publications
1
12
0
Order By: Relevance
“…This finding is in line with the results reported by Vervliet and Indekeu, 33 who found that avoidance behaviour can reoccur after successful fear extinction, when the avoidance response became available again. Also, the return of the availability to avoid may have acted as a negative occasion setter as described by De Houwer et al 5,6 Regarding our fourth hypothesis, we found that more frequent avoiders reported higher pain expectancies and pain-related fear during the free-choice test phase. This result suggested that not only acquired avoidance behaviour by itself can increase pain expectancy and pain-related fear but also the frequency of performing the avoidance behaviour has an effect on those measures.…”
Section: Discussionsupporting
confidence: 58%
“…This finding is in line with the results reported by Vervliet and Indekeu, 33 who found that avoidance behaviour can reoccur after successful fear extinction, when the avoidance response became available again. Also, the return of the availability to avoid may have acted as a negative occasion setter as described by De Houwer et al 5,6 Regarding our fourth hypothesis, we found that more frequent avoiders reported higher pain expectancies and pain-related fear during the free-choice test phase. This result suggested that not only acquired avoidance behaviour by itself can increase pain expectancy and pain-related fear but also the frequency of performing the avoidance behaviour has an effect on those measures.…”
Section: Discussionsupporting
confidence: 58%
“…Despite subsequent replication and extension of those findings (Declercq and De Houwer, 2008 ), more recent evidence (e.g., Declercq and De Houwer, 2011 ) argues against the negative occasion setting account, as the property of selective transfer could also be explained by the lesser reinforcement of C compared to A and B during the first phase of the experiment. Still, despite this limitation, insights from the negative occasion setting account could prove clinically important.…”
Section: Informational Factors In Avoidance Learningmentioning
confidence: 92%
“…Informational factors also play an important role in the avoidance learning theory of De Houwer and colleagues (De Houwer et al, 2005 ; Declercq and De Houwer, 2008 ). According to those authors, an avoidance response serves as a signal that a CS is not going to be followed by an aversive event, which in associative learning language is called a “negative occasion setter” (see Holland, 1992 ; Schmajuk and Holland, 1998 , for reviews on occasion setting).…”
Section: Informational Factors In Avoidance Learningmentioning
confidence: 99%
“…However, the tone in itself does not predict the presence or absence of the US. Particularly interesting for the present topic is that Declercq and De Houwer (2008) recently found that a behavioral response in the form of avoidance can have occasion-setting properties. Translating this to our patient Simon, he believes lifting heavy things (the CS) predicts spinal injury (the US), unless he keeps his back straight (subtle avoidance behavior; feature X).…”
Section: Avoidance Behavior and Its Relation To Fearmentioning
confidence: 97%